Risk assessment in a hypothetical network pipeline in UK transporting carbon dioxide. (November 2016) - Vianello, Chiara; Mocellin, Paolo; Macchietto, Sandro; Maschio, Giuseppe
Abstract: With the advent of Carbon Capture and Storage technology (CCS) the scale and extent of its handling is set to increase. Carbon dioxide (CO2 ) capture plants are expected to be situated near to power plants and other large industrial sources. Afterward CO2 is to be transported to storage site using one or a combination of transport media: truck, train, ship or pipeline. Transport by pipeline is considered the preferred option for large quantities of CO2 over long distances. The hazard connected with this kind of transportation can be considered an emerging risk and is the subject of this paper. The paper describes the Quantitative Risk Assessment of a hypothetical network pipeline located in UK, in particular the study of consequences due to a CO2 release from pipeline. The risk analysis highlighted that some sections of pipeline network cross densely populated areas. For this reason, some changes in the original path of the network have been proposed in order to achieve a significant reduction in the societal risk. Highlights: The analysis identifies distances of damage depending on some parameters. We calculate local and societal risks for CO2 pipeline configurations. We analyse rerouting of network and risk assessment. Can be used as a decision planning for limiting risks during restore operations.